Olfactory deficits decrease the time resolution for trigeminal lateralization - Oleszkiewicz, A.; Meusel, T.; Güpfert, M.; Westermann, B.; Hummel, T.; Welge-Lüssen, A. (International journal of psychophysiology, 2017)
To date the temporal resolution of the detection of almost simultaneously applied intranasal trigeminal stimuli is unknown. The aim of our study was to examine this temporal resolution in an/hyposmic subjects, who are known to have reduced trigeminal sensitivity and compare it with healthy controls. Participants were 20 posttraumatic an/hyposmic patients, and 23 healthy controls (matched with regard to sex and age). Olfactory function was tested psychophysically using the Sniffin´ Sticks test battery. Bilateral trigeminal stimulation was carried out using a birhinal high-precision olfactometer. The trigeminal stimulus used was CO₂ 60% v/v, the interstimulus interval ranged from 28 to 32s, stimulus duration was 200ms. Time-lags tested between right and left side of stimulation were at 40, 80, 120, 160 and 200ms. Subjects raised their left or right hand to indicate the side on which the stimulus had been perceived first. In both groups the accuracy in the trigeminal lateralization task increased with the time-lag but normosmic subjects significantly outperformed an/hyposmics in the 200ms time-lag condition. Normosmics significantly exceeded 50% chance level at the time-lag of 80ms, whereas an/hyposmics were only able to score above chance starting from 120ms time-lag. Lateralization scores significantly decreased with age. At a time lag of 200ms intranasal trigeminal stimuli can be lateralized. The reduced trigeminal sensitivity in patients with anosmia or hyposmia leads to an increased time lag required for correct perception of intranasal, almost simultaneously, applied stimuli. •Study examines temporal resolution of trigeminal stimuli in relation to olfactory deficits.•Twenty an-/hyposmics and 23 controls performed trigeminal lateralization task with intervals of 40, 80, 120, 160 and 200ms.•Accuracy increased with time-lag but normosmics significantly outperformed an-/hyposmics in the 200ms time-lag.•Reduced trigeminal sensitivity increases time-lag required for correct perception of almost simultaneously applied stimuli.